The Importance of physical activity in the treatment of hemophilia - Ziojła-Lisowska, Kinga; Cieplińska, Aleksandra; Kuzio, Agnieszka; Jama, Grzegorz (Quality in Sport, 2024)
Hemophilia is a genetically determined bleeding disorder characterized by a tendency for spontaneous bleeding, mainly into the joints, which can lead to arthropathy and significantly reduce the quality of a patient’s life. The objective of this paper is to review the published literature on the impact of physical activity on the course of the disease and its role in current therapeutic protocols. Online databases were used to search for literature. The retrieved articles were analyzed. The review mainly included literature published after 2016. In the past, physical exercise was not recommended for people with hemophilia, primarily due to concerns about joint bleeding and the development of hemophilic arthropathy. Currently, regular, moderate physical activity plays a crucial role in the management of hemophilia, helping to strengthen muscles and improve joint stability, which can reduce the risk of bleeding. This shift in perspective is largely due to the availability of effective therapeutic options, mainly involving the replacement clotting factors. However, entirely new hopes for a permanent cure and the maintenance of physical fitness are brought by modern gene therapy treatments. Physical activity is essential for maintaining the health and fitness of individuals with hemophilia, and most exercises are safe due to effective prophylactic treatment. In addition to the benefits for joint health, regular exercise also helps prevent many lifestyle-related diseases.